Acute toxicity of dipfluzine and its effects on isolated vascular smooth muscle - WANG Yong-li; LI Yun-shan; FU Shao-xuan; JIN Sheng (Acta Pharmacologica Sinica; Vol 11, No 1 (January 1990): Acta Pharmacologica Sinica, 2016)
Dipfluzine (Dip) is a new derivative of cinnarizine (Cin) first developed by Department of Chemistry, Beijing University. Dip showed a dose-dependently inhibitory effect on both KCl- and NE-induced contraction in the rabbit aortic rings. It was more effective in suppressing the contractile response evoked by KCl than that by NE. Dip also inhibited the KCl-induced contraction in porcine basilar, coronary and radial arteries. Their pD2' values were 5.7 +/- 0.6, 5.4 +/- 0.4 and 4.6 +/- 0.5 respectively. The selectivity of Dip for vasodilation was proved by higher pD2' value of the basilar artery than that of the coronary and radial arteries, and this selectivity of Dip was more significant than that of Cin. The acute iv LD50 of Dip and Cin in mice were 37 and 36 mg/kg, respectively.